Comparative safety of different sodium-glucose transporter 2 inhibitors in patients with type 2 diabetes: a systematic review and network meta-analysis of randomized controlled trials - Li, Chun Xing; Liu, Li Yan; Zhang, Chen Xiao; Geng, Xu Hua; Gu, Si Meng; Wang, Yu Qiao; Liu, Hua; Xie, Qing; Liang, Shuo (Frontiers in Endocrinology, 2023)
Backgrounds: The safety of different sodium-glucose transporter 2 (SGLT-2) inhibitors remains uncertain due to the lack of head-to-head comparisons.Methods: This network meta-analysis (NMA) was performed to compare the safety of nine SGLT-2 inhibitors in patients with type 2 diabetes (T2DM). PubMed, Embase, Cochrane Central Register of Controlled Trials and ClinicalTrials.gov were searched for studies published in English before August 30, 2022. Published and unpublished randomized controlled trials (RCTs) comparing the safety of individual SGLT-2 inhibitors in patients with T2DM were included. A Bayesian NMA with random effects model was applied. Subgroup and sensitivity analyses were performed. The quality of the evidence was evaluated using the Confidence in Network Meta-Analysis framework.Results: Nine SGLT-2 inhibitors were evaluated in 113 RCTs (12 registries) involving 105,293 adult patients. Reproductive tract infections (RTIs) were reported in 1,967 (4.51%) and 276 (1.01%) patients in the SGLT-2 inhibitor and placebo groups, respectively. Furthermore, pollakiuria was reported in 233 (2.66%) and 45 (0.84%) patients, respectively. Compared to placebo, a significantly higher risk of RTIs was observed with canagliflozin, ertugliflozin, empagliflozin, remogliflozin, dapagliflozin, and sotagliflozin, but not with luseogliflozin and ipragliflozin, regardless of gender. An increased risk of pollakiuria was observed with dapagliflozin [odds ratio (OR) 10.40, 95% confidence interval (CI) 1.60-157.94) and empagliflozin (OR 5.81,. Remogliflozin (OR 6.45,) and 4 4 dapagliflozin (OR 1.33, 95%CI 1.10-1.62) were associated with an increased risk of urinary tract infections (UTIs). Instead, the included SGLT-2 inhibitors had a protective effect against acute kidney injury (AKI). No significant differences were found for hypovolemia, renal impairment or failure, fracture, diabetic ketoacidosis (DKA), amputation, and severe hypoglycemia between the SGLT-2 inhibitor and the placebo groups.Conclusion: In patients with T2DM, dapagliflozin was associated with an increased risk of RTIs, pollakiuria, and UTIs. Empagliflozin increased the risk of RTIs and pollakiuria. Remogliflozin increased the risk of UTIs. None of the SGLT-2 inhibitors showed a significant difference from the placebo for hypovolemia, renal impairment or failure, fracture, DKA, amputation, and severe hypoglycemia. The findings guide the selection of SGLT-2 inhibitors for patients with T2DM based on the patient's profiles to maximize safety.